2019
DOI: 10.1111/roiw.12411
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Being, Deprivation, and the Great Recession in the U.S.: A Study in A Multidimensional Framework

Abstract: We study changes in social well-being and deprivation in the U.S. during the Great Recession and the subsequent recovery. We outline an analytical framework for measuring well-being and deprivation in a multidimensional fashion when data on achievement in each dimension is assumed to be ordinal and binary in nature. We use data from the American Community Survey between 2008 and 2015 and find that there was a decline in social well-being and a rise in social deprivation in the U.S. during the recession followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Dhongde and Haveman [ 4 ] found that between 2008 and 2013, about 40% of Hispanics were multidimensional poor compared with 14% in the general population. Similarly, Dhongde et al [ 5 ] found deprivation levels to be one of the highest among Hispanics between 2008 and 2015.…”
Section: Deprivation By Race and Ethnicitymentioning
confidence: 94%
See 2 more Smart Citations
“…Dhongde and Haveman [ 4 ] found that between 2008 and 2013, about 40% of Hispanics were multidimensional poor compared with 14% in the general population. Similarly, Dhongde et al [ 5 ] found deprivation levels to be one of the highest among Hispanics between 2008 and 2015.…”
Section: Deprivation By Race and Ethnicitymentioning
confidence: 94%
“…This paper uses a set of indices proposed by Alkire and Foster [ 24 ]. Except for Dhongde et al (2019) [ 5 ] who propose a different set of indices, all of the previous studies estimating multidimensional poverty in the United States, have used the Alkire and Foster [ 24 ] indices (e.g. see [ 4 , 6 , 7 ]) largely because of their ease of interpretation.…”
Section: Framework For Multidimensional Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We may note here that a number of such norms are also discussed in the literature on the measurement of multidimensional deprivation and well-being. Dhongde, Li, Pattanaik, and Xu (2016), Dhongde, Pattanaik, and Xu (2017) and Pattanaik and Xu (2018) are among the important recent contributions to this literature. (We are indebted to an anonymous referee for these references.)…”
Section: Relation To Other Work and Concluding Observationsmentioning
confidence: 99%
“…Dhongde and Haveman (2017),Dhongde et al (2019),Glassman (2019),Mitra and Brucker (2019).10 Dhongde and Haveman (2017) andDhongde et al (2019) use ACS data; Glassman (2019) also uses ACS but combines information from CPS Mitra and Brucker (2019). is the only study which has used only CPS data.…”
mentioning
confidence: 99%